Recommender System in E-Commerce : Bringing Revolution in Marine Product Industry - Pal, Subhabaha; Pal, Satyabrata (Indian Journal of Computer Science, 2018)
E-commerce business world is evolving at a fast pace and to remain relevant in the business, the ecommerce world started introducing new tools for enhancing customer experience. Recommender System is one such tool. This paper discusses how Recommender system works and major types of Recommender systems which are currently in use. This paper also discusses some applications of the Recommender system in the marine product industry.